2009
DOI: 10.1017/s0212610900000811
|View full text |Cite
|
Sign up to set email alerts
|

The Expansion of Mass Education in Twentieth Century Latin America: A Global Comparative Perspective

Abstract: This paper studies the expansion of mass education in Latin America in the twentieth century from a global comparative perspective. The paper argues that expansion in terms of enrolment and attainment levels was quite impressive. A comparative analysis of the grade enrolment distribution demonstrates, however, that the rapid expansion of primary school enrolment did not correspond with an equally impressive improvement in educational quality. The persistently large tertiary education bias in public education s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 28 publications
2
42
0
6
Order By: Relevance
“…The power inequality secures the existence of the inegalitarian agrarian structure (De Janvry, 1981). Similar structures are observed in some regions of sub-Saharan Africa (Frankema, 2010).…”
Section: A Comparative Perspectivesupporting
confidence: 82%
See 1 more Smart Citation
“…The power inequality secures the existence of the inegalitarian agrarian structure (De Janvry, 1981). Similar structures are observed in some regions of sub-Saharan Africa (Frankema, 2010).…”
Section: A Comparative Perspectivesupporting
confidence: 82%
“…The impact of land inequality on urban distribution has been examined in several prior studies (Engerman and Sokoloff, 2002;Galor and Zeira, 1993;Galor and Tsiddon, 1996;Galor, Moav and Vollrath, 2004;Bourguignon and Verdier, 2000;Frankema, 2009;Wegenast, 2009). These studies focus on institutions, pointing out in particular that greater wealth inequality would lead to institutions that bias education capabilities and policies against the poor.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, despite some improvements during the 20th Century, it has been suggested that these changes were not enough in terms of the quantity and equity of public spending and not outstanding from an international perspective [108,109]. In the Chilean case, for instance, it was only in 1920, more than a century after independence, that compulsory primary education was introduced.…”
Section: A Knowledge Gapmentioning
confidence: 99%
“…[108] Likewise, despite some improvements during the 20th century, it has been suggested that these changes were not enough in terms of the quantity and equity of public spending and not outstanding from an international perspective. [109,110] In the Chilean case, for instance, it was only in 1920, more than a century after independence, that compulsory primary education was introduced. As late as the 1950s, approximately 9% of the school age population never attended school; 30% of those who entered the first grade abandoned school within the first two years and only 28.6% of the school age population completed their primary education.…”
Section: A Knowledge Gapmentioning
confidence: 99%